The prevalence and risk factors of sexual dysfunction among diabetic and non diabetic female patient in HUSM - Ismail @ Daud, Adibah Hanim (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2010)
Objective To determine the prevalence of female sexual dysfunction among diabetes and non diabetes women, compare the sexual dysfunction domain in the two group and also to determine the risk factors of female sexual dysfunction in both diabetic and non diabetic group Research Design and Methods Data were collected from 178 diabetic women and 175 non diabetic women using Malays Version of Female Sexual Function Index. The socio demographic characteristic, marital profile, medical illness and husband health status of the participants were recorded. Glyceamic control was recorded based on HbA 1 c. Results The prevalence of sexual dysfunction among diabetic women was 26.4 % and among non diabetic women was 20.0 %. Arousal disorder was reported in 28.7% of diabetic women and only 17.1 % of non diabetic women have the same problems. (p value 0.040). Sexual satisfactions disorder found in diabetic female and non diabetic female were 15.2% and 8.0% respectively (p value 0.042). Age more than 40 years, unhappy marriages, duration of marriage more than 20 years, lower HDL level, married to husband with hypertension and duration of diabetes more than 1 0 years were the significant associated factors for sexual dysfunction among diabetic women. Among non diabetic women, unhappy marriage, less sexual intercourse ( < 2 time per week) and presence of hypertension were the significant associated factors of sexual dysfunction. Conclusion The prevalence of sexual dysfunction was not significantly different between diabetic and non diabetic women. Diabetic women significantly reported more sexual arousal and satisfaction problems compared with non diabetic women. The duration of diabetic was inversely correlated with women sexual function. Unhappy marriages have negative effect on sexual function in both diabetic and non diabetic women.